الماء ودلالاته في القرآن الكريم: دراسة موضوعية تحليلية - جدي، فاتن محمد علي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The purpose of this thesis is to analytically and objectively study Qur'anic verses where water is mentioned, supported by scientific facts proven by research and studies. It aims to clarify the meaning of water linguistically as well as idiomatically. The study also reveals numerous types of water in the Qur'an and their scientific connotatios, and compiles the properties of water, showing the unique chemical, physical, geographical, and therapeutic properties Allah has given to water. The study discusses two issues pertaining to water pollution and water shortage and the Islamic solutios to these problems. The study points out the important role of water in life; its role in making things alive, in the revival of the land and the production of plants from it, in the human and animal watering, and in cleansing the body and objects. The study adapted both the inductive and analytical methods. One of the findings of the study is the meaning of water in the Qur'an has broader and deeper significance than the linguistic meaning. A functional definition for water is proposed by the researcher and a linguistic analysis of the word “water” is addressed in terms of its indefinite and definite forms and their significance, and verbs linked to the noun “water” and their implications. The study also shows that there are several types of water mentioned in the Qur'an that human knowledge has yet to realize their meaning and essence. The word rain contained in the Qur'an is counted and its scientific implications are analyzed. The researcher confirms that Allah the Almighty has granted water unique properties that make it alive without which its manifestations disappear. The study is concluded with the analysis of water symbolism in the Holy Qur'an through the analysis of Qur'anic proverbs that have been coined for water.